The First Textbook on Technical Writing - Schmelzer, Richard W. (Journal of Technical Writing and Communication, 1977)
Richard W. Schmelzer, the author of this article on the first textbook written for technical writing classes, knows his subject from firsthand experience. He was one of the first teachers assigning The Preparation of Reports to future engineers. In this paper he pays tribute to Dr. Ray Palmer Baker, an early authority on modern technical communication and the author of The Preparation of Reports.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMjE5MC8xYzljLTExdjctcTdoMy1rOTh0